2004
DOI: 10.1093/oxfordjournals.schbul.a007088
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortical Dysfunction in Akinetic Catatonia: A Functional Magnetic Resonance Imaging Study During Negative Emotional Stimulation

Abstract: Catatonia is a psychomotor syndrome characterized by concurrent emotional, behavioral, and motor anomalies. Pathophysiological mechanisms of psychomotor disturbances may be related to abnormal emotional-motor processing in prefrontal cortical networks. We therefore investigated prefrontal cortical activation and connectivity patterns during emotional-motor stimulation using functional magnetic resonance imaging (FMRI). We investigated 10 akinetic catatonic patients in a postacute state and compared them with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 81 publications
5
87
0
2
Order By: Relevance
“…While our study focused on a priori regions of interest specifically located within frontal cortex, preliminary post hoc analyses provided some evidence that other regions-such as the parahippocampal cortex and occipital cortex-were affected by the reward manipulation. Techniques such as structural equation modeling might offer important tools for understanding the relationship between ventral prefrontal regions and other regions involved in affective processing (Northoff et al, 2004). Map of mean raw signal intensity values; the coverage of these functional images is depicted in a voxelwise map.…”
Section: The Role Of the Ventral Frontal Cortexmentioning
confidence: 99%
“…While our study focused on a priori regions of interest specifically located within frontal cortex, preliminary post hoc analyses provided some evidence that other regions-such as the parahippocampal cortex and occipital cortex-were affected by the reward manipulation. Techniques such as structural equation modeling might offer important tools for understanding the relationship between ventral prefrontal regions and other regions involved in affective processing (Northoff et al, 2004). Map of mean raw signal intensity values; the coverage of these functional images is depicted in a voxelwise map.…”
Section: The Role Of the Ventral Frontal Cortexmentioning
confidence: 99%
“…Reports on brain areas involved in catatonia are scarce. Available data point to frontal lobe regions, such as the pronounced catatonia in a case of butterfly glioma of the frontal corpus callosum (6) or frontal activation in akinetic catatonic patients detected by functional MRI (7).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on 'anterior cingulate cataplexy' date from half a century ago and refer to a loss of muscle tonus commonly induced by strong emotion (Ethelberg, 1950;Fuster, 1955;Levin, 1953). More recent investigations indeed showed that negative emotional stimulation induced hyperactivation in orbitofrontal cortex and a shift of main activation to ACC www.elsevier.com/locate/biopsycho Biological Psychology 71 (2006) [316][317][318][319][320][321][322][323][324][325] and medial prefrontal cortex in catatonic patients (Northoff et al, 2004). Also in animals the role of the ACC in the modulation of motor inhibition and freezing reactions has been well established (e.g.…”
Section: Introductionmentioning
confidence: 99%